Analysis for a molten carbonate fuel cell - C. J. van Duijn; Joseph D. Fehribach (Electronic Journal of Differential Equations, 1993)
for a molten carbonate electrode of a fuel cell. The model consists of two coupled second-order ordinary differential equations, one for the concentration of the reactant gas and one for the potential. Restricting ourselves to the case of a positive reaction order in the Butler-Volmer equation, we consider existence, uniqueness, various monotonicity properties, and an explicit approximate solution for the model. We also present an iteration scheme to obtain solutions, and we conclude with a few numerical examples.